The influence of training and development on employee productivity at the Ronggo Mukti batik company - Lailatul Mukarromah; Muh. Maftuh Al-Fiqri; Lailatul Fitriyah; Beny Anggara; Andy Danuarta; Yeni Kartikawati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to examine the effect of training and development programs on employee productivity at the Ronggo Mukti Batik Company. In an increasingly competitive business environment, improving the quality of human resources is a crucial element in enhancing a company's competitiveness. This study employed a qualitative method with a descriptive approach. Information was collected through intensive interviews and direct observation of employees to understand their personal experiences, perspectives, and behavioral transformations following the training and development program. The findings revealed that training and development positively impacted employee productivity, reflected in improved skills, job insight, and increased motivation to carry out responsibilities. Structured training initiatives and ongoing development activities have proven effective in enhancing employee capabilities and work enthusiasm, thus supporting improvements in individual and overall organizational performance. These results emphasize the urgency of a company's commitment to human resource management as a strategy for achieving long-term goals.